The social sciences and the millenium bug - Elisa Reis P. (Revista Brasileira de Ciências Sociais, 1999)
At the end of her term, departing Anpocs president (1996-98) lectures on the contemporary challenges social sciences face. She suggests that the scope and magnitude of current changes have often been ignored by social scientists who therefore risk converting their analysis into superfluous enterprises. Unless we manage to address what really matters to real people, she argues, we will not be able to ask the proper questions that make our business worthwhile.